Eras pada Lower Abdominal Surgery - Pratomo, Bhirowo Y.; Sudadi; Gentong, Metia Gledis G. (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2020)
Enhanced Recovery After Surgery (ERAS) also known as fast track surgery or Enhanced Recovery Protocol (ERP) is a multimodal-based perioperative management designed to reduce morbidity, length of hospitalization, improve postoperative recovery time and minimize postoperative complications. Key elements of the ERAS protocol include pre-operative counseling, nutrition optimization, analgesic standards and anaesthesia regimens and early mobilization. Lower abdominal surgery and colorectal resection have traditionally been associated with high morbidity and length of hospital stay. ERAS has been shown to improve postoperative recovery, reduce length of stay and increase early return to normal function when compared to traditional colorectal surgical protocols. Recommendations for anaesthesia treatment in patients undergoing gastrointestinal surgery in the ERAS program are issued in an integrated protocol, which can facilitate the involvement of anesthesiologists in the implementation of the ERAS program.